How can I show that $\lnot \exists x P(x) \vdash \forall x\lnot P(x)$ ?

Because I want to show: $\lnot \exists x (P(x) \lor R(x)) \vdash \forall x \lnot R(x)$

My idea: maybe a proof by contradiction would work...


For $¬∃xP(x)⊢∀x¬P(x)$, it is enough to assume $P(x)$ :

1) $¬∃xP(x)$ --- premise

2) $P(x)$ --- assumed [a]

3) $∃xP(x)$ --- from 2) by $∃$-introduction

4) $\bot$ --- from 1) and 3)

5) $¬P(x)$ --- from 2) and 4) by $¬$-introduction, discharging [a]

6) $∀x¬P(x)$ --- from 5), by $∀$-introduction.


Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.